Pengaruh konsentrasi polifenol pada produksi asam laktat dari substrat menggunakan Rhizopus oryzae - Maulana Gilar Nugraha; Siti Syamsiah; Agus Prasetya (Jurnal Rekayasa Proses, 2015)
Polyphenol is antioxidant compound naturally present in plants e.g in cacao shell (Thebrema cacao L.). The cacao shell has high cellulose content (30-50%), and therefore it is potential to be converted into various types of products. Cellulose could be hydrolyzed to produce glucose, and glucose could be fermented to become lactic acid. However, polyphenol presence in the cacao shell is suspected to be inhibitory to fermentation process. This research aimed to figure out the polyphenol effect in lactic acid fermentation with glucose as substrate by the fungus Rhizopus oryzae. Polyphenol concentrations in the fermentation broth were varied with value of 0, 10, 15, and 20 g/L. Along the course of the experiment, lactic acid concentration was measured by means of gravimetric and conductometric method. Fungus growth was measured through dry mass method while consumption of glucose was observed by glucose determination with Nelson-Samogyi method. The results showed that polyphenol presence in fermentation system would decrease lactic acid production from 40.55 g/L (system without polyphenol) to 18.24 g/L (system with 20 g/L polyphenol). Microbe growth inhibition also observed from 3.68 g/L (system without polyphenol) to 0.51 g/L (system with 20 g/L polyphenol). However, polyphenol presence did not affect the total glucose consumption. Final glucose concentrations in all system were about 10.94 to 19.28 g/L. Some possible factors for this phenomenon were glucose conversion to another product and glucose utilization for cell maintenance. This research also found that the best kinetic model to represent the fermentation system was uncompetitive inhibition model.